Obstetric and Neonatal Outcome among Women Presenting with Reduced Fetal Movements in Third Trimester - Madiha Abbasi, Erum Samreen Siddiqui, Amna Shafiq, Aurooj Fatima, Nasreen Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Reduced fetal movements (RFM) define as the decrease in the normal movement of a developing fetus in the womb. It is important to monitor fetal movements during pregnancy because these can be an indication of the baby’s health and wellbeing. The management of RFM in the third trimester includes fetal monitoring Study design: It is a prospective observational study conducted for the duration of one year from June 2021 to May 2022. Material and Methods: The study was conducted on 150 patients who visited Obs/ Gynae department of LUMHS Hyderabad, Jamshoro and MBBS Medical College Mirpur Azad Kashmir during the course of 1 year. Average age of patients was 32 years with 30 of them reported to have primary education while the remaining had secondary or higher level of studies. The BMI of 40 patients was more than 30 kg/m2 while 35 had BMI between 25-30 kg/m2. Results: The neonatal outcomes in patients were evaluated after reduced fetal growth. There were 60 patients with one episode of RFM and 72 were with multiple RFM episodes. Mortality rate, abnormal CTG (Cardiotocography), neonatal unit (NNU) admission, severe morbidity, low Apgar score and Birth weight <10th centile were some of the outcomes studied Conclusion: RFM leads to high risk of still birth, Caesarean and severe morbidity for the new born. Although on episode of RFM can’t be considered as a necessary evidence of compromised birth but multiple episodes indicates towards several risks related to pregnancy. Keywords: Reduced fetal movements, neonatal outcomes and third trimester.